Siblings as socialization agents: Exploring the role of 'sibship' in the consumer socialization of children. Issue 5 (11th May 2015) - Kerrane, Ben; Bettany, Shona M; Kerrane, Katy
Abstract : Purpose: – This paper explores how siblings act as agents of consumer socialisation within the dynamics of the family network. Design/methodology/approach: – Key consumer socialisation literature is reviewed, highlighting the growing role that siblings play in the lives of contemporary children. The authors' interpretive, exploratory study is introduced which captures the voices of children themselves through a series of in-depth interviews. Findings: – A series of socialisation behaviours are documented, with children working in both positive and negative ways to develop the consumer skills of their siblings. A fourfold typology of sibling relationships is described, capturing the dynamic of sibling relationships and parental approaches to parenting vis-à-vis consumption. This typology is then used to present a typology of nascent child consumer identities that begin to emerge as a result of socialisation processes within the family setting. Research limitations/implications: – The role siblings play in the process of consumer socialisation has potentially important implications in terms of the understanding of the socialisation process itself, and where/how children obtain product information. Scope exists to explore the role siblings play as agents of consumer socialisation across a wider variety of family types/sibling variables presented here (e.g. to explore how age/gender shapes the dynamics of sibling–sibling learning). Originality/value: – Through adopting a networked approach to family life, the authors show how the wider family dynamic informs sibling–sibling relationships and resulting socialisation behaviours. The findings problematise the view that parents alone act as the main conduits of consumer learning within the family environment, highlighting how parent–child relationships, in turn, work to inform sibling–sibling socialisation behaviour and developing consumer identities.